TV DOCUMENTARY FILM JOURNAL NEGLASARI RIVER "RIVER OF A THOUSAND BENEFITS" - Tuty Mutiah, Mutiah; Andi Setyawan; Fajar Muharam; Jaka Atmaja; Marlina Rahmi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
This documentary was made to document the activities of the community along the Neglasari riverbank which is considered unique and interesting in the midst of modern settlement development. Neglasari River is an irrigation river that is part of the Cisadane River. The existence of this river is very close to the activities and needs of the surrounding community. The main function of Neglasari River is as an irrigation river that flows vegetable and rice plantations along the riverbanks. Vegetable plantations are the main commodity of this area, so irrigation from the Neglasari river is vital to the sustainability of plantations and agriculture of the surrounding community. In addition to these benefits, the Neglasari river is also a resource that is widely used by the surrounding community to meet their daily needs, such as bathing, washing clothes, washing vegetables from the plantation harvest, playing facilities for children, and even washing motorized vehicles. These community activities are carried out not because they do not have water resources at home, even some residents' houses look quite livable with adequate toilet facilities. This is due to cultural factors that have long been practiced by the surrounding community. Since childhood they have used the river to fulfill their daily needs, and this is still maintained and carried out until now. he main factor of community activities in the river is still ongoing because they can interact with fellow residents, and are not bored if they have to take care of household chores at home alone.